2000
DOI: 10.1111/j.1745-4514.2000.tb00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxbdant Properties of Oregano (Origanum Vulgare) Leaf Extracts

Abstract: We tested the antioxidant properties of both aqueous and methanolic extracts of oregano (origanum vulgare) They proved to be effective in the inhibition of all phases of the peroxidative process: first neutralizing free radicals (superoxide anion, hydroxyl radical and 1,1‐diphenyl‐2‐picrylhydrazyl radical), then blocking peroxidation catalysis by iron (through iron‐chelating and iron‐oxidizing properties), and finally through interruption of lipid‐radical chain reactions (chain‐breaking activity). Their anti‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(113 citation statements)
references
References 17 publications
(14 reference statements)
4
105
0
4
Order By: Relevance
“…The control Sandesh sample had an activity of 5%, Sandesh with rice bran had an activity of 51%, Sandesh with oregano extract had an activity 74% and the final product with extract and bran together had an activity of 81%. The DPPH activity of oregano extract was found to be 84% which is in agreement with Cervato et al, (2000). Thus, the activity of extract decreased when added to Sandesh.…”
Section: Sensory Evaluation Of Sandesh Samplessupporting
confidence: 74%
See 1 more Smart Citation
“…The control Sandesh sample had an activity of 5%, Sandesh with rice bran had an activity of 51%, Sandesh with oregano extract had an activity 74% and the final product with extract and bran together had an activity of 81%. The DPPH activity of oregano extract was found to be 84% which is in agreement with Cervato et al, (2000). Thus, the activity of extract decreased when added to Sandesh.…”
Section: Sensory Evaluation Of Sandesh Samplessupporting
confidence: 74%
“…Addition of extract at initial stage of Sandesh preparation showed similar antioxidant activity in Sandesh samples. This might be due to the fact that the phytochemicals, which are responsible for the antioxidant effect of oregano extract, are not heat sensitive (Cervato et al, 2000).…”
Section: Sensory Evaluation Of Sandesh Samplesmentioning
confidence: 99%
“…The bioavailability of oregano constituents in chicken tissues cannot be directly demonstrated because adequate analytical methodology has not been developed yet. However, it has been reported that α-tocopherol, a major natural chainbreaking antioxidant in the cell membranes, provides protection against early events in lipid oxidation at the site where it is initiated, while oregano constituents can be effective in the inhibition of all phases of the peroxidative process by first neutralising free radicals, then blocking peroxidation catalysis by iron and, finally, through chain-breaking activity (Cervato et al, 2000). A synergistic effect of dietary oregano essential oil and α-tocopheryl acetate supplementation on the oxidative stability of raw and cooked turkey meat has also been previously reported by Botsoglou et al (2003c).…”
Section: Discussionmentioning
confidence: 99%
“…Antuono, Galletti, & Bocchini, 2000 ;Dadalioğlu & Evrendilek, 2004;Ozel & Kaymaz, 2004;Figuérédo, Cabassu, Chalchat, & Pasquier, 2006;Azizi et al, 2009;Bisht, Chanotiya, Rana, & Semwal 2009) and antioxidant capacity of oregano (Cervato, Carabelli, Gervasio, Cittera, Cazzola, & Cestaro, 2000;Exarchou, Nenadis, Tsimidou, Gerothanassis, Troganis, & Boskou, 2002;Dorman et al, 2003;Kulisic, Radonic, Katalinic, & Milos, 2004;Capecka et al, 2005;Shan, Cai, Sun, & Corke 2005;A. Nurmi, T. Nurmi, Mursu, Hiltunen, & Voutilainen, 2006;Amarowicz et al, 2009), less has been done to systematically investigate the impact of solvent type and extraction technique on bioactive components of oregano (Exarchou et al, 2002;Boydag, Kurkcuoglu, Ozek, & Baser, 2003).…”
Section: Introductionmentioning
confidence: 99%